A survey of mental health literacy in Japanese high school teachers - Yamaguchi, Satoshi; Foo, Jerome Clifford; Kitagawa, Yuko; Togo, Fumiharu; Sasaki, Tsukasa (BMC psychiatry, 2021)
School teachers are well-positioned to recognize mental health problems in their students and to help them seek appropriate help. Therefore, teachers need to have high levels of mental health literacy (MHL). In East Asia, however, few studies have examined MHL levels in teachers. In this study, MHL levels were investigated in Japanese teachers.
Gesehen am 18.01.2023